Halogen bonding: the sigma-hole - Clark, Timothy; Hennemann, Matthias; Murray, Jane S.; Politzer, Peter (Journal of Molecular Modeling, 2007)
Halogen bonding refers to the non-covalent interactions of halogen atoms X in some molecules, RX, with negative sites on others. It can be explained by the presence of a region of positive electrostatic potential, the sigma-hole, on the outermost portion of the halogen's surface, centered on the R-X axis. We have carried out a natural bond order B3LYP analysis of the molecules CF3X, with X = F, Cl, Br and I. It shows that the Cl, Br and I atoms in these molecules closely approximate the s(2)p(x)(2)p(y)(2)p(z)(1) configuration, where the z-axis is along the R-X bond. The three unshared pairs of electrons produce a belt of negative electrostatic potential around the central part of X, leaving the outermost region positive, the sigma-hole. This is not found in the case of fluorine, for which the combination of its high electronegativity plus significant sp-hybridization causes an influx of electronic charge that neutralizes the sigma-hole. These factors become progressively less important in proceeding to Cl, Br and I, and their effects are also counteracted by the presence of electron-withdrawing substituents in the remainder of the molecule. Thus a sigma-hole is observed for the Cl in CF3Cl, but not in CH3Cl.
Keywords: Halogen bonding; Sigma-hole; Electrostatic potential; DFT